The concentration of MMP-9 and the effects of intravenousanaesthetics on the efficacy of electroconvulsive therapy in patientswith drug-resistant depression - Permoda-Pachuta, Agnieszka; Skibińska, Maria; Dmitrzak-Węglarz, Monika; Rybakowski, Filip (Current Problems of Psychiatry, 2021)
Introduction. This study attempts to assess the concentration of intracellular matrix metalloproteinase (MMP-9) before and after the treatment of depressive episodes with ECT therapy and also to correlate the concentration of this enzyme with the use of commonly used general anaesthetics.Materials and methods. The study group comprised of 37 patients hospitalized in the Department of Adult Psychiatry in Poznan, with a diagnosis of episodes of drug-resistant depression during the course of bipolar and unipolar affective disorders, and who were being treated using electroconvulsive therapy. For the purpose of inducing anaesthesia during the procedure propofol was used in 10 cases, thiopental in 9 cases. Propofol was alternated with ketamine in a further 10 cases and thiopental was alternated with ketamine in another 9 cases. In order to assess the intensity of depression symptoms, the 17 point Hamilton depression scale was used, immediately before commencing ECT therapy, and one day after its completion. The serum concentration of MMP-9 was determined before and after the series of ECT treatments. In order to assess the serum concentration of MMP-9, an ELISA immunoenzymatic method was applied.Results. In this study, a significant reduction of MMP-9 concentration was noted after therapy, relative to the starting concentration, in the serum of patients suffering from depressive episodes resulting from either unipolar or bipolar affective disorders. These results correlated with improved psychiatric state, as assessed by the Hamilton scale. A significantly lower MMP-9 concentration was noted in the serum of patients given alternating thiopental and ketamine anaesthesia.Conclusions. This study suggests the importance of the enzyme as a biological marker for the effective treatment of depression. Furthermore, the choice of general anaesthetic applied during ECT also plays a role.